Multiplicity Result of Positive Solutions for Nonlinear Differential Equation of Fractional Order - Yang Liu; Zhang Weiguo (Abstract and Applied Analysis)
We investigate the existence of multiple positive solutions for a class of boundary value problems of nonlinear differential equation with Caputo’s fractional order derivative. The existence results are obtained by means of the Avery-Peterson fixed point theorem. It should be point out that this is the first time that this fixed point theorem is used to deal with the boundary value problem of differential equations with fractional order derivative.